Pharmacogenovigilance in Drug Safety: Knowledge, Attitudes and Practice Among Final-Year Medical and Pharmacy Students in Peninsular Malaysia - Mainul, Haque; Yau, Adamu (2016)
The need for adoption of pharmacogenomics and pharmacovigilance into practice among healthcare professionals has been increasing as this provides greener future to individualized medicine and drug safety. This study aimed to assess the knowledge, attitude and practice of final-year Medicine and Pharmacy students towards Pharmacogenomics, and pharmacovigilance in drug safety at some public and private universities Peninsular Malaysia. A cross-sectional study was conducted using a self-administered questionnaire (Cronbach's alpha coefficient 0.822) among 465 participants, yielding a response rate of 380 (82.1%) over the period of the study. The analysis of the continue variables was done using the student t-test and one-way ANOVA. The associations between categorical variables were analyzed using the Chi-square test. The independent t-test revealed that, the mean knowledge and attitude scores among final-year pharmacy students were 89.20±8.86% and 73.7±6.59%, and that of final-year medical students were 84.95±13.2% and 69.7±7.74% respectively, with a statistically significant difference (p-value<0.001 at 95% CI). A low level of practice was observed with a statistically significant difference between a pharmacy and medical students (P<0.05). Findings revealed that the questionnaire was a valid and reliable instrument that could be used for the same purpose under the same condition. The majority demonstrated good knowledge and attitude towards pharmacogenovigilance in drug safety, but with a low level of practice. These findings show the readiness of the participated final-year medical and pharmacy students towards the pharmacogenomic based challenges and integration of pharmacogenomics into practice.